A path analytic approach to the validation of a taxonomic system for classifying child molesters - Prentky, Robert A. (Journal of quantitative criminology, 1989)
This study examined the validity of the most recent revision of a taxonomy for child molesters developed at the Massachusetts Treatment Center (MTC:CM3). The taxonomy is distinguished both from earlier versions of this system and from other systems, by three major changes: (a) the partitioning of the “regressed/fixated” dichotomy into two separate factors-level of social competence and degree of fixation on children, (b) the introduction of a new type (“narcissistic”) to fill an empirically determined gap between the object-related offender and the antisocial, exploitative offender, and (c) the differentiation of the violence in the sexual offense into nonsadistic and sadistic components. MTC:CM3 was used to classify 177 child molesters who were committed to the Treatment Center. Variables coded from the clinical files were rationally grouped according to developmental period and subjected to principal-components analysis (PCA). The PCA-derived components then were entered into a series of regression analyses. The resulting three path models indicated that the new subtypes created by the aforementioned refinements had distinct developmental courses and adult adaptations.